GEODYNAMIC ASPECTS IN THE STUDY OF COMPLEX MINING AND GEOLOGICAL CONDITIONS FOR DRILLING INTO OIL-AND-GAS RESERVOIRS IN THE RIPHEAN CARBONATE ROCKS: AN OVERVIEW OF THE PROBLEM AS EXEMPLIFIED BY THE DEPOSITS IN THE BAIKIT PETROLIFEROUS DISTRICT - A. G. Vakhromeev; S. A. Sverkunov; V. M. Ivanishin; R. K. Razyapov; E. V. Danilova (Геодинамика и тектонофизика, 2017)
The practical aspects are discussed in the geodynamic studies of the massive vugular-fractured oil-and-gas reservoir in the Riphean carbonate rocks of the Yurubcheno-Tokhoma oil-gas-condensate field in the Baikit petroliferous district. This field is a part of the Yurubcheno-Tokhoma zone that includes the Kuyumba oil-and-gas field, Omorinsk gas-condensate field (a satellite field) and the promising Kamovsky, Vaividinsky, Shushuksky, Seismorazvedochny and Kordinsky areas [Kontorovich et al., 1988]. Potential recoverable resources are predicted to amount to two billion tonnes of fuel equivalent in this zone, which area exceeds 60000 km2, also known as the Kuyumba-Yurubcheno-Tokhoma oil-and-gas accumulation zone [Trofimuk, 1992; Trofimuk et al., 1989; Kharakhinov, Shlenkin, 2011]. A key factor for the economically effective development of the deposits in the Baikit petroliferous district is the feasibility of efficient primary recovery of oil and gas by horizontal wells to be drilled to large depths to reach the complex fractured natural reservoirs in the Riphean carbonate rocks. This paper discusses one field as an example from the Baikit petroliferous district and summarizes the results of the detailed studies of the geodynamic and hydrodynamic conditions of the oil-gas-condensate reservoir in the Riphean rocks. The reported results are compared with the actual field data, including the annulus pressure sensor measurements [Vakhromeev et al., 2013, 2015, 2016]. The previous findings are confirmed and extended: when vertical fractures are penetrated by drilling, and the hydraulic pressure variations amount to 0.5–1.5 % of the formation pressure, the effect of alternating mud-loss / kicks occurs in the near-wellbore zone due to the high permeability of the reservoir and the lack of the skin-effect in the bottomhole zone [Sverkunov et al., 2016]. The allowable ranges of the variations in the dynamic bottomhole pressure are estimated and justified for primary penetration into the oil-saturated vugular-fractured strata. Within an allowable range of pressure rates, a horizontal well can be drilled with minimal complications caused by alternating adjustable mud-loss and kick effects. Based on our study results, prerequisites are determined for developing the new technology of penetrating into pay zones in carbonate vugular-fractured reservoirs with anomalously low formation pressure rates.